2016
DOI: 10.21037/qims.2016.03.03
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative 3D breast magnetic resonance imaging fibroglandular tissue analysis and correlation with qualitative assessments: a feasibility study

Abstract: Background: The amount of fibroglandular tissue (FGT) has been linked to breast cancer risk based on mammographic density studies. Currently, the qualitative assessment of FGT on mammogram (MG) and magnetic resonance imaging (MRI) is prone to intra and inter-observer variability. The purpose of this study is to develop an objective quantitative FGT measurement tool for breast MRI that could provide significant clinical value.Methods: An IRB approved study was performed. Sixty breast MRI cases with qualitative … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
20
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(20 citation statements)
references
References 16 publications
0
20
0
Order By: Relevance
“…So US can not accurately measure the volume of the lesion and not accurately observe the spatial distribution of lesional blood flow (13). Breast MRI is the most sensitive examination for breast tumor detection and it can be used to detect the spatial relationship between the lesion and the surrounding tissue, the spatial distribution of lesional blood flow as well (14)(15)(16)(17)(18). What's more, MRI can be used to assess tissue necrosis after ablation by administrating contrast agent (19,20).…”
Section: Discussionmentioning
confidence: 99%
“…So US can not accurately measure the volume of the lesion and not accurately observe the spatial distribution of lesional blood flow (13). Breast MRI is the most sensitive examination for breast tumor detection and it can be used to detect the spatial relationship between the lesion and the surrounding tissue, the spatial distribution of lesional blood flow as well (14)(15)(16)(17)(18). What's more, MRI can be used to assess tissue necrosis after ablation by administrating contrast agent (19,20).…”
Section: Discussionmentioning
confidence: 99%
“…Breast cancer risk primarily depends on family history, hormonal risk factors and genetic mutations (eg, BRCA 1, 2) and current clinical practice employs several risk reduction strategies that target these factors, such as lifestyle changes, chemoprevention, and invasive surgical measures including prophylactic mastectomy and salpingo‐oophorectomy . While these measures are often effective at reducing breast cancer risk, they can be associated with substantial side effects, which considerably reduce quality of life …”
mentioning
confidence: 99%
“…Several studies have shown a strong correlation between FGT and mammographic density . FGT can be evaluated three‐dimensionally on magnetic resonance imaging (MRI), providing a more accurate assessment of the total epithelial and stromal elements . Similar to mammographic density, the amount of FGT is also modifiable, with many studies showing the effects of chemoprevention medications on the amount of FGT …”
mentioning
confidence: 99%
See 2 more Smart Citations